The Results of Urine Toxicology Tests in Children With Drug Abuse Poisoning in Loghman Hakim Hospital in 2021 - Farnaghi, Fariba; Pournasiri, Zahra; Alinejad, Saeideh; Owliaey, Hamid (Journal of Pediatric Nephrology, 2025)
Background and Aim: Correct and rapid diagnosis and timely treatment of acute poisoning are of great importance, mainly in legally crucial drugs of abuse poisoning. Urine drug toxicology (UDT) is an available, rapid, and cheap diagnostic tool. This study aims to evaluate the results of this study in children with acute poisoning. Methods: In this prospective descriptive cross-sectional study conducted on the urine toxicology results of children admitted to Loghman-Hakim Hospital due to poisoning with opioids and cannabis in 2021, UDT was performed for all patients. Demographic data, type, method and time of poisoning, time of urine sample collection, urine pH and specific gravity (SG), and urine toxicology results were collected and statically analyzed using SPSS version 26. Results: A total of 137 children were evaluated. The mean age was 4.11±3.45 years, and 49.6% were boys. UDTs were positive in 106 of 137 patients (77.4%). The most common poisoning was methadone (61.32%) followed by opium (19.71%). No significant statistical difference was observed between the time of taking the urine sample as well as the type, pH, and specific gravity (SG) (P>0.05). Of the 84 methadone-poisoned patients, 74 (88%) tested positive for UDT. The positive results for opium, cannabis, and buprenorphine were 77.77%, 33.33%, and 50%, respectively. Conclusion: In our study, methadone was the most common poisoning, with urine toxicology showing a positive result in 88% of cases.